The Suitability Of Harm Reduction Programme In Controlling HIV/AIDS Cases; A Syari'ah Perspective - Yasmin Hanani Mohd Safian; Farah Salwani Muda @ Ismail, (Universiti Sains Islam Malaysia, 2024)
This research attempts to study the applicability of the proposed Harm Reduction Programme from the perspective of SharFah. This programme launched by the Ministry of Health is a as an effort to curb the spreading of HIVIAIDS in the country. This programme which includes the needle and syringes exchange programme and the free condom programme ignites much controversies among Muslim. Thus, this study attempts to confirm any SharTah rulings applicable in justifying this proposed solution. The principle of 'darrlrat' and the principle of 'rnaglahah' are used to justify the applicability of this programme. The researchers also rely on the information and material collected from primary data and secondary data collected from the Ministry of Health, journals, websites and others. The analytical study is made accordingly. The study found that the proposed programme is suitable to be implemented based on the principle of 'darirat ' and the principle of 'maglahah '. In this case, the 'maglahah ' (interest) of the family will be protected. It is also believed that by tolerating lesser harm, a greater harm will be eliminated. This study also supports the proposed programme provided that it is the last resort after any other means to reduce HIVIAIDS cases have taken place. However, the permissibility of the said programme is only valid if certain conditions are met. This research is believed to be able to provide solutions to clear the doubts concerning Harm Reduction Programme. It is also hoped that it will be a significant reference and guide to the authority to implement the proposed programme in order to curb the increasing number of HIVIAIDS in Malaysia and at the same time the implementation is in accordance with the spirit of Shari'ah.